Study Analisis Penurunan Tanah Lempung Lunak dan Lempung Organik Menggunakan Pemodelan Matras Beton Bambu dengan Tiang - Iswan Iswan; Lusmeilia Afriani; Ikratul Herman (UNIVERSITAS LAMPUNG, 2016)
This study aims to determine the magnitude of the decline in clay, by comparing the reduction in soft clay soil of the village Belimbing Sari and organic clay from the village of Beteng Sari, using concrete reinforcement mats and bamboo poles to increase the carrying capacity of the land, because the clay when getting the imposition of the will experience a significant drop. This research was conducted by making test Boks modeling land subsidence, and perform impairment testing ground that has been given concrete reinforcement using a bamboo mat with a pole on soft clay soil of the village Belimbing Sari and organic clay from the village of Beteng Sari. Using weights ranging from 0.2 kg/cm2, 0.3 kg/cm2, 0.4 kg/cm2, 0.5 kg/cm2. Testing was conducted on the impairment testing ground to seek consolidation coefficient (Cv), congestion coefficient of volume (Mv), compression index (Cc) and coefficient of compression (Av). Based on the research results, the test box, the decline in clay is lower than the original soil testing, this happens because the test soil reinforcement box has been given a concrete form bamboo mat with a pole. From this it can be concluded that the carrying capacity of the clay to get better after being given reinforcement.